Nanozyme-based wearable biosensors for application in healthcare - Yingcong Zhang; Yiran Yang; Zhixin Yin; Lin Huang; Jiayi Wang (iScience)
Summary: Recent years have witnessed tremendous advances in wearable sensors, which play an essential role in personalized healthcare for their ability for real-time sensing and detection of human health information. Nanozymes, capable of mimicking the functions of natural enzymes and addressing their limitations, possess unique advantages such as structural stability, low cost, and ease of mass production, making them particularly beneficial for constructing recognition units in wearable biosensors. In this review, we aim to delineate the latest advancements in nanozymes for the development of wearable biosensors, focusing on key developments in nanozyme immobilization strategies, detection technologies, and biomedical applications. The review also highlights the current challenges and future perspectives. Ultimately, it aims to provide insights for future research endeavors in this rapidly evolving area.